Plasma microRNA-9 as a diagnostic and prognostic biomarker in patients with esophageal squamous cell carcinoma. (August 2017) - Cui, Yuantao; Xue, Yuan; Dong, Shangwen; Zhang, Peng
Purpose: Emerging evidence indicates that circulating microRNAs (miRs) might act as noninvasive biomarkers for cancer diagnosis and prognosis. We examined the expression pattern and clinical significance of plasma miR-9 in patients with esophageal squamous cell carcinoma (ESCC). Methods: Venous blood samples (6 mL) were collected from 131 patients with ESCC and 131 healthy controls, and the plasma miR-9 concentration was detected by reverse transcription polymerase chain reaction. The association of plasma miR-9 expression with clinicopathologic factors and survival of patients with ESCC was evaluated. Receiver operating characteristic (ROC) curve analysis was applied to evaluate the clinical value of plasma miR-9 for ESCC diagnosis. Results: The plasma miR-9 expression levels in patients with ESCC were significantly upregulated compared with normal controls. High plasma miR-9 concentrations were significantly correlated with poor tumor differentiation, large tumor size, deep local invasion, lymph node metastasis, advanced clinical stage, and poor survival. ROC curve analysis showed that the plasma miR-9 concentration could efficiently distinguish patients with ESCC from healthy controls. Multivariate survival analysis confirmed plasma miR-9 as an independent prognostic factor for ESCC. Conclusions: Plasma miR-9 expression was upregulated in ESCC and might act as a novel diagnostic and prognostic biomarker.